The ecological causes of individual specialisation - Araujo, Marcio S. [UNESP]; Bolnick, Daniel I.; Layman, Craig A. (Wiley-Blackwell, 2011)
Many generalist populations are composed of specialised individuals, whose niches are small subsets of the population niche. This 'individual specialisation' is a widespread phenomenon in natural populations, but until recently few studies quantified the magnitude of individual specialisation and how this magnitude varies among populations or contexts. Such quantitative approaches are necessary for us to understand how ecological interactions influence the amount of among-individual variation, and how the amount of variation might affect ecological dynamics. Herein, we review recent studies of individual specialisation, emphasising the novel insights arising from quantitative measures of diet variation. Experimental and comparative studies have confirmed long-standing theoretical expectations that the magnitude of among-individual diet variation depends on the level of intra and interspecific competition, ecological opportunity and predation. In contrast, there is little empirical information as to how individual specialisation affects community dynamics. We discuss some emerging methodological issues as guidelines for researchers studying individual specialisation, and make specific recommendations regarding avenues for future research.
Keywords: Competition; ecological opportunity; ecology of individuals; food webs; niche variation hypothesis; optimal foraging theory; predator-prey interactions; stable isotopes